The IT Governance Role on Internal Accountability and Performance in Higher Education Institutions: Testing the Intervening Role of Performance Measurement System and IT Capabilities - Sofyani, Hafiez; Pratolo, Suryo; Putra, Wahyu Manuhara (Jurnal Dinamika Akuntansi, 2023)
Purpose: This study examined the role of IT governance practices on internal accountability and performance of higher education institutions (HEIs) through two intervening variables, namely performance measurement system (PMS) and IT capabilities. Also, it examined the IT governance role in PMS implementation and IT capabilities.Method: This study was conducted at HEI on the Island of Java using a survey approach with hypothesis testing by employing a structural equation modelling-partial least square technique (SEM-PLS). 149 HEIs were successfully included in this study.Findings: The results implied that IT governance could directly promote good PMS implementation and IT capabilities. Furthermore, IT governance was found not to be directly related to internal accountability and performance of HEIs, but it had to go through the PMS implementation as intervening. These results indicate that good IT governance did not necessarily provide added value to HEIs if it is not accompanied by a good PMS implementation. Novelty: This study presents empirical evidence that addresses the research gap on the role of IT governance on internal accountability and performance by putting the PMS policy as intervening variable. This study also presents novelty in terms of setting, namely HEIs where competitive advantage is needed to maintain viability, in the midst of increasingly stringent HEIs competition.